2018
DOI: 10.3389/fpsyg.2018.00065
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Italian Tinnitus Questionnaire Short Form (TQ 12-I) as a Brief Test for the Assessment of Tinnitus-Related Distress: Results of a Cross-Sectional Multicenter-Study

Abstract: Objectives: The use of reliable and valid psychometric tools to assess subjectively experienced distress due to tinnitus is broadly recommended. The purpose of the study was the validation of the Italian version of Tinnitus Questionnaire 12 item short form (TQ 12-I) as a brief test for the assessment of patient reported tinnitus-related distress.Design: Cross-sectional multicenter questionnaire study.Setting: Tinnitus Center, European Hospital (Rome), the Department of Otorhinolaryngology, “Guglielmo da Salice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
0
13
0
3
Order By: Relevance
“…The results of our study showed good internal consistency, test-retest reliability and clinical validity for the TQ 12-T. Internal consistency was excellent (>0.70) for TQ 12-T. For validation purposes, the Mini TQ was performed to correlate with other questionnaires such as the Perceived Stress Scale (PSS 14) [13] , Multidimensional Health Locus of Control Scale (MΗLoC) [13] , Brief Symptom Inventory (BSI) [18] , Short Form Health Survey (SF 36) [18] , TQ [15] and THI [17,18] in previous studies. All questionnaires showed good correlation with TQ 12.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The results of our study showed good internal consistency, test-retest reliability and clinical validity for the TQ 12-T. Internal consistency was excellent (>0.70) for TQ 12-T. For validation purposes, the Mini TQ was performed to correlate with other questionnaires such as the Perceived Stress Scale (PSS 14) [13] , Multidimensional Health Locus of Control Scale (MΗLoC) [13] , Brief Symptom Inventory (BSI) [18] , Short Form Health Survey (SF 36) [18] , TQ [15] and THI [17,18] in previous studies. All questionnaires showed good correlation with TQ 12.…”
Section: Discussionmentioning
confidence: 68%
“…So far, the Mini TQ has been translated into several languages, including Portuguese [12] , Greek [13] , Arabic [14] , Dutch [15] , Chinese [16] , Malay [17] and Italian. [18] However, there is still a shortage of translated versions of the TQ 12 to be accepted as a worldwide questionnaire. The purpose of this study was to investigate the reliability and validity of the Turkish version of the Mini-Tinnitus Questionnaire (TQ 12-T).…”
Section: Introductionmentioning
confidence: 99%
“…Tinnitus distress was also measured with the Italian 12 item short form of the Tinnitus Questionnaire (TQ 12-I) 34 . For the TQ 12-I, good reliability and validity were reported.…”
Section: Methodsmentioning
confidence: 99%
“…Several questionnaires have now been developed and validated for assessment of tinnitus complaints: Tinnitus Handicap Questionnaire 2 , Tinnitus Reaction Questionnaire 3 , Tinnitus Handicap Inventory (THI) 4 , Tinnitus Questionnaire (TQ) 5 and its short form, Mini-TQ 6 and the Tinnitus Primary Function Questionnaire 7 . The THI and Mini-TQ have also been validated in their Italian language versions 8,9 . More recently Moschen et al validated the Italian version of the Chronic Tinnitus Acceptance Questionnaire (CTAQ-I) 10 .…”
Section: Introductionmentioning
confidence: 99%